Plastic Optical Fibre As A Sensor For Turbidity Measurement - Yeoh, Stephenie (2015)
The aim of this study is to develop a turbidity sensor using plastic optical fibre (POF) to perform measurement of turbidity in water samples. A turbidity sensor is operated by measuring the return signal that is caused by scattering of suspended particles present in turbid water. The designed experiment was conducted using a near infrared (NIR) laser diode as light source to emit NIR light into aqueous samples via POFs and to couple the back reflected signal to the spectrometer.